Iron oxide recovery from fayalite in water vapor at high temperature - Chen J.H.; Mi W.J.; Chen H.Y.; Li B.; Chou K.C.; Hou X.M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The oxidation behavior of fayalite (Fe2SiO4) in water vapor at 1000°C was investigated. The phase constitution and microstructure of the solid products were characterized using X-ray diffraction (XRD) and scanning electron microscopy (SEM) with energy dispersive spectrometer (EDS). The gas product was continuously measured online by a gas analyzer. The results showed that fayalite was completely decomposed into magnetite (58.8 wt%), hematite (21.6 wt%) and silica (19.6 wt%) at 1000 °C for 40 min under water vapor condition. Compared with the result obtained in dry air, water vapor could promote fayalite to transform into magnetite by decreasing oxygen fugacity. In addition, the iron oxide product was further enriched via alkaline cleaning in 1 mol/L NaOH. As for the gas product, the hydrogen production capacity reached 24.41 mL/g when exposed to 50 vol% water-50 vol% Ar at 1000°C for 40 min.